Comparative Discrimination of Life’s Simple 7, Life’s Essential 8, and Life’s Crucial 9: Evaluating the impact of added complexity on mortality prediction - Xu Zhu; Iokfai Cheang; Yiyang Fu; Sitong Chen; Gengmin Liang; Huaxin Yuan; Ling Zhu; Haifeng Zhang; Xinli Li (BMC Medicine)
Abstract Background Cardiovascular health (CVH) is a key determinant of mortality, but the comparative effectiveness of different CVH metrics remains uncertain. Life’s Simple 7 (LS7) evaluates seven domains: smoking, body mass index, physical activity, total cholesterol, blood pressure, fasting glucose, and diet. Life’s Essential 8 (LE8) adds sleep health, while Life’s Crucial 9 (LC9) further includes mental health. This study aimed to assess whether the additional components in LE8 and LC9 enhance mortality prediction compared to LS7. Methods Data from 22,382 participants in the NHANES 2005–2018 were analyzed. Cox proportional hazards regression models were used to evaluate the associations between the scores of these metrics and all-cause, cardio-cerebrovascular disease (CCD), and CVD mortality. The predictive performance of each metric was assessed via receiver operating characteristic (ROC) curves and area under the curve (AUC) values. Results The participants had a mean age of 45.23 ± 0.23 years, and 51.53% were female. During a median follow-up of 7.75 (4.42–11.08) years, there were 1,483 all-cause deaths, 405 CCD deaths, and 337 CVD deaths. Compared with participants with LS7 scores ≤ 4, those with scores ≥ 11 had a 65% (HR = 0.35 [0.25–0.50]) lower risk of all-cause mortality, a 66% (HR = 0.34 [0.16–0.73]) lower risk of CCD mortality, and a 61% (HR = 0.39 [0.18–0.85]) lower risk of CVD mortality. Similar trends were observed for LE8 and LC9. The AUC for LS7 (0.68 [0.66–0.70]) was slightly greater than that for LE8 (0.67 [0.65–0.69], P = 0.007) and LC9 (0.67 [0.65–0.69], P = 0.019) in predicting all-cause mortality at 5 years; however, the overall predictive performance was nearly identical across all three metrics. Furthermore, the addition of LS7 (AUC = 0.84 [0.82–0.86], P < 0.001), LE8 (AUC = 0.84 [0.82–0.86], P < 0.001), and LC9 (AUC = 0.84 [0.83–0.86], P < 0.001) to the baseline model (AUC = 0.83 [0.82–0.85]) significantly improved all-cause mortality predictions at 5 years; however, the actual gains in predictive performance were marginal. Conclusions LS7, LE8, and LC9 all predict mortality effectively. Given its simpler scoring and fewer components, LS7 demonstrates comparable predictive performance to LE8 and LC9, making it a more practical tool for clinical and public health applications.